2018
DOI: 10.3233/blc-170144
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Correlates of In Vitro Responses to Dacomitinib and Afatinib in Bladder Cancer

Abstract: Background:The HER family of proteins (EGFR, HER2, HER3 and HER4) have long been thought to be therapeutic targets for bladder cancer, but previous clinical trials targeting these proteins have been disappointing. Second generation agents may be more effective.Objective:The aim of this study was to evaluate responses to two second-generation irreversible tyrosine kinase inhibitors, dacomitinib and afatinib, in bladder cancer cell lines.Methods:Cell lines were characterized by targeted next generation DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 73 publications
2
13
1
Order By: Relevance
“…There were an additional 13 mutations present in 1-2 cell lines, including inactivating CDKN2A, RB1, and PTEN mutations with LOH and activating oncogenic ERBB2, AKT1, HRAS, and KRAS mutations. We did not observe increased ERBB2 inhibitor (lapatinib, canertinib, sapatinib, mubritinib, GW2580, dacomitinib, and WZ4002) sensitivity in ERBB2 activating mutant cell lines, in contrast to similar studies using 2D cell culture [ 31 ]. The AKT1 mutated PDX cell line (BC8149) is sensitive to many PI3K/AKT/mTOR inhibitors, while HRAS and KRAS mutated lines (T-24 and UM-UC-3) are largely insensitive to most PI3K/AKT/mTOR inhibitors.…”
Section: Resultscontrasting
confidence: 93%
“…There were an additional 13 mutations present in 1-2 cell lines, including inactivating CDKN2A, RB1, and PTEN mutations with LOH and activating oncogenic ERBB2, AKT1, HRAS, and KRAS mutations. We did not observe increased ERBB2 inhibitor (lapatinib, canertinib, sapatinib, mubritinib, GW2580, dacomitinib, and WZ4002) sensitivity in ERBB2 activating mutant cell lines, in contrast to similar studies using 2D cell culture [ 31 ]. The AKT1 mutated PDX cell line (BC8149) is sensitive to many PI3K/AKT/mTOR inhibitors, while HRAS and KRAS mutated lines (T-24 and UM-UC-3) are largely insensitive to most PI3K/AKT/mTOR inhibitors.…”
Section: Resultscontrasting
confidence: 93%
“…2a) 11,12 . To examine which isoforms are expressed within basal and luminal human bladder cancers and understand their relationship with ATDC, we examined expression of each TP63 isoform in the TCGA bladder cancer cohort and in 19 human bladder cancer cell lines 26,27 . We found that the dNp63 N terminal isoforms were the most commonly expressed isoforms in both human TCGA specimens, representing 99% of total TP63 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that CHD5 plays an essential role in cancer development. The expression of multiple genes that regulate pathways in the tumourigenic process was modulated by CHD5 [ 31 ]. Apoptosis, cellular senescence and neonatal death will occur by excessive activation of these tumour-suppressive pathways, dependent on p53, p19 and p16.…”
Section: Discussionmentioning
confidence: 99%